PENERAPAN MODEL PROBLEM BASED LEARNING DENGAN MEDIA FLASHCARD UNTUK MENINGKATKAN HASIL BELAJAR IPS PADA SISWA KELAS IV SD NEGERI 4 TAMANWINANGUN TAHUN AJARAN 2015/2016 - Ali, Fajar (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Problem Based Learning Model Using Flashcard Media in Improving Social Study Learning for the Fourth Grade Students of SD Negeri 1 Krandegan in the Academic Year of 2015/2016. The objectives of this research is to improve social study learning outcomes for the fourth grade students. Subjects of the research were fourth grade students of SD Negeri 4 Tamanwinangun in academic year of 2015/2016 totaling 25 students. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Each cycle consisted two meetings including planning, action, observation, and reflection. Source of data were derived from students, teacher, and observer. Techniques of collecting data were observation, interview, and test. Validity of data in this research was analyzed using triangulation of sources and triangulation of technique. The results of this research showed that the application of Problem Based Learning model using flashcard media can improve social study learning outcomes and process. Keywords: PBL, flashcard, social study Abstrak: Penerapan Model Problem Based Learning dengan Media Flashcard untuk Meningkatkan Hasil Belajar IPS pada Siswa Kelas IV SD Negeri 4 Tamanwinangun Tahun Ajaran 2015/2016. Tujuan penelitian ini untuk meningkatkan hasil belajar IPS pada siswa kelas IV. Subjek penelitian adalah siswa kelas IV SD Negeri 4 Tamanwinangun yang berjumlah 25 siswa. Penelitian kolaboratif ini dilaksanakan dalam tiga siklus. Setiap siklus terdiri dari perencanaan, pelaksanaan, observasi, dan refleksi. Sumber data penelitian adalah siswa, guru, dan observer. Teknik pengumpulan data dengan observasi, wawancara, dan tes. Validitas data menggunakan triangulasi sumber dan teknik. Analisis data meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan penggunaan model PBL dengan media flashcard dapat meningkatkan proses dan hasil belajar IPS. Kata Kunci: PBL, Flashcard, IPS